南极普里兹湾及其邻近海域细菌生产力的研究 - 邱雨生; 黄奕普; 陈敏; 刘广山 (国家海洋局极地考察办公室;中国极地研究所, 2003)
本文阐述了在中国第 1 6次南极科学考察期间 ( 1 999/ 2 0 0 0南半球夏季 )运用3H 胸腺嘧啶核苷示踪法研究南极普里兹湾及其邻近海域细菌生产力的分布特征。结果表明 :该海区细菌生产力比较低 ,变化范围在 4.5— 1 91ngC·dm- 3·h- 1 ,平均为 5 0 .4ngC·dm- 3·h- 1 ,其水平与Ross海相当。细菌生产力的变化较好地反映了浮游植物变化的特性 ,BP与PP的比值为 0 .41。表层水体中BP与DOC的分布特征呈反相关关系。普里兹湾及邻近海域细菌生产力、初级生产力及溶解有机碳之间的关系表明 ,细菌的活动受浮游植物活跃程度及其它环境条件的影响 【英文摘要】 Bacterial productivity were estimated by 3H thymidine uptake in the Prydz Bay and its adjacent waters during the 16th Chinese National Antarctic Research Expedition (CHINARE) in the austral summer of 1999/2000. The bacterial productivity ranged from 4.5 to 191 ngC·dm -3 ·h -1 , with an average of 50.4 ngC·dm -3 ·h -1 in waters studied, which was relatively low and similar to those in the Ross Sea. The mean ratio of BP to PP was 0.41 in our study area. The maximum value of ba. 国家自然科学基金 ( 4 983 60 1 0 );; 科技部公益研究专项 ( 2 0 0 1DIA5 0 0 40 )资助